ANALISIS PENGENDALIAN KUALITAS PRODUK BUMBU TABUR DENGAN MENGGUNAKAN METODE FAULT TREE ANALYSIS DAN TAGUCHI - Fuji Rahayu Wilujeng; Danil Christiyadi (Universitas Bunda Mulia, 2022)
Product quality depends on adequate human resources, methods, raw materials, environment, equipment and machinery. PT. XYZ has implemented a product control system with the aim that the products produced are in accordance with the established standards. Through quality control, it is hoped that the company can improve the effectiveness of control in preventing the occurrence of defective products. with the fault tree analysis method in order to produce a product defect flow diagram with the aim of knowing the factors that cause the product to become defective, knowing the types of defects that most often appear along with the factors causing them and providing suggestions for improvements on how to reduce failures in the product manufacturing process. . and by using the Taguchi Method is a method of quality control before the process takes place or often called off-line quality control which is very effective in improving quality and also reducing costs.